Intranasal Use of Prescription Stimulants Among Adults Aged 18 to 30: Results From A Crowdsourcing Platform. Issue 1 (January 2023) - Vosburg, Suzanne K.; Faraone, Stephen V.; Riley, Elizabeth; Whitaker, Timothy; Kardish, Jessica; Baker, David; Kollins, Scott H.; Rush, Craig R.
Objective: Few studies of prescription stimulant non-oral, non-medical use (NMU) (defined by use not as prescribed) have been conducted in adults beyond the college population. The purpose of this study was to characterize prescription stimulant non-oral use, specifically intranasal (IN) use (snorting) in young adults. Method: Amazon's MTurk platform was used to recruit participants for an online survey. Data were collected from March to April 2020. Results: Thirty-two percent ( n = 157) of survey respondents ( N = 975), aged 18 to 30, reported IN prescription stimulant use (average of 32.1 episodes of lifetime IN use). Adderall was the most-reported prescription stimulant used intranasally (89.2%). Most IN users (82%; n = 68) reported spending no more than 5 minutes tampering with prescription stimulants. Intranasal users said they would take the medication orally if unable to tamper or manipulate medication for IN use. Conclusion: These data help quantify a complex public health issue of ongoing IN use of prescription stimulants and suggest a potential role for manipulation-deterrent medications.